Student perspectives on the value of research participation - Roberts, Lynne; Allen, Peter (Cambridge Scholars Publishing, 2012)
Undergraduate (UG) students are the most frequently used participants in psychological research. Here we report on the results of a qualitative exploration of the research participation experience, as seen from the perspective of UG psychology students. Following retrospective ‘opt out’ consent procedures, 143 first and third year psychology students’ responses to a research methods exam question, “You’ve been invited to participate in a number of research projects this semester; what have you learned from this experience?” were de-identified, transcribed, and thematically analysed. The results provide a rich, nuanced and contextually sensitive account of the perceived value of the research participation experience. The major theme to emerge was that participating in research provides psychology students with increased insight into the research process. We propose that this educational gain may be further enhanced through greater integration of research participation with the teaching of research methods.